Rubric Design: A Designer’s Perspective - William Furman (Journal of the Scholarship of Teaching and Learning, 2024)
The rubric, a canonical matrix of criteria presented to students as the road map to academic success. An “Ah-ha” moment, “that is what I’m looking for” utopia for the fresh-minted instructor. While rubrics provide the possibility for solving the complexity of some teaching problems, like many fuzzy oases we have come to know rubrics as a thinly veiled tools that are as useful as they are well designed. If you ever have designed rubrics, you know well they resolve some issues but present many more. They contain a conundrum of specific questions: What do I want my students to know? How do I want them to perform? How am I going to evaluate them? What am I attempting to transfer? Reveal? Show? What am I teaching? As many instructors would attest, these questions are not always easy. Creating rubrics can be difficult, very time-consuming, and can feel like a paradox. But in the end, they can also provide real value to the student and instructor. This reflective essay takes on the design and development of the rubric, challenging the notion there are different types of rubrics or inherent evaluation methodologies, offers an alternative layout, and reviews rubrics through the designer’s lens, approaching them through concept development and design thinking.